A Guideline for Reporting and Assessment of Health Interventions Using Mobile Phones. - Karataş, Nimet; Dalgıç, Ayşegül İşler (Journal of Education & Research in Nursing / Hemşirelikte Eğitim ve Araştırma Dergisi, 2022)
Background: In recent years, especially considering today's conditions, the use of mobile health applications that offer the remote health education, management, and monitoring has been increasing. Aim: The aim of this study is to present the Turkish form of the mobile health evidence reporting and assessment mobile health checklist, which is a guide for the full and accurate reporting of mobile health applications provided via mobile phones, to the national literature. Methods: In the first stage of the mobile health evidence reporting and assessment checklist consisting of 16 items, a Turkish translation text was created by 2 authors, and in the second stage, the views of 10 academicians from different disciplines were examined with Kendall's W coefficient. Results: It was determined that there was agreement among the observers on intelligibility and clarity of items (W = 0.556, P = .000). The minimum set of information required to describe the content, context, and how the mobile health application was implemented was provided with 16 items and explanatory examples regarding how the technological elements are reported, how the content is tested, how participants are involved, and so on were provided on Turkish form of the mERA checklist. Conclusion: It is thought that mobile health Evidence Reporting and Assessment will ensure the active use of standards that can increase the quality of future publications and bring them to an acceptable level by eliminating the possible evidence gaps in the reporting of research on mobile health applications. With this article, it is envisaged, as first nurses, that all researchers working in the field of health informatics will contribute to the reporting of study evidence.